Archaeology of Orissa - Basa, Kishor K.; Mohanti, Pradeep (Delhi : Pratibha Prakashan, 2003)
Contributed articles
Includes bibliographical references and index
Keywords: Excavations (Archaeology) -- India -- Orissa; Orissa (India) -- Antiquities